Synthesis and characterization of mono and polymeric cyclopalladated compounds: Crystal and molecular structure of [{Pd(dmba)(ONO2)}(2)(mu-pz)] center dot H2O (pz = pyrazine) - Ananias, Sandra R. [UNESP]; Ferreira, Janaina G. [UNESP]; Mauro, Antonio Eduardo [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Klein, Stanlei Ivair [UNESP]; Santos, Regina H. A. (Pergamon-Elsevier B.V. Ltd, 2009)
In the treatment of cyclometallated dimer [Pd(dmba)(mu-Cl)](2) (dmba = N,N-dimethylbenzylamine) with AgNO3 and acetonitrile the result was the monomeric cationic precursor [Pd(dmba)(NCMe)(2)](NO3) (NCMe=acetonitrile) (1). Compound 1 reacted with m-nitroaniline (m-NAN) and pirazine (pz), originating [Pd(dmba)(ONO2)(m-NAN)] (2) and [{Pd(dmba)(ONO2)}(2)(mu-pz)] center dot H2O (3), respectively. These compounds were characterized by elemental analysis, IR and NMR spectroscopy. The IR spectra of (2-3) display typical bands of monodentade O-bonded nitrate groups, whereas the NMR data of 3 are consistent with the presence of bridging pyrazine ligands. The structure of compound 3 was determined by Xray diffraction analysis. This packing consists of a supramolecular chain formed by hydrogen bonding between the water molecule and nitrato ligands of two consecutive [Pd-2(dmba)(2)(ONO2)2(mu-pz)] units. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Cyclometallated; Palladium; Nitro compounds